Gynecological & Psychological Morbidities after Hysterectomy-A Retrospective Observational Study (KYAMC Journal, 2017)
The aim of this study was to find out the gynecological & psychological morbidities after hysterectomy operation due to different types of gynecological diseases in admitted patients of Khwaja Yunus Ali Medical collage & Hospital, a rural tertiary hospital in Bangladesh. In this retrospective observational study total 190 gynecological patients were evaluated in 4 years who were admitted either from OPD or through emergency. Most of the patients were operated due to uterine fibroid, DUB, chronic cervicitis, CIN, PID with chronic pelvic pain, genital prolapse, cervical carcinoma, ovarian tumor etc. After a period of hysterectomy operation those patients were suffered from chronic pelvic pain 3%, vaginal discharge 2%, dyspareunia 1%, vault prolapse .5%, early appearance of post menopausal syndrome 13% & some psychological complaints like anxiety disorders 5% & depressive illness 2%. Those patients were observed in OPD of KYAMCH during followed up.KYAMC Journal Vol. 4, No.-1, July 2013, Page 348-352